Guidelines for the management of ulcerative colitis. Recommendations of the Polish Society of Gastroenterology and the Polish National Consultant in Gastroenterology - Eder, Piotr; Łodyga, Michał; Gawron-Kiszka, Magdalena; Dobrowolska, Agnieszka; Gonciarz, Maciej; Hartleb, Marek; Kłopocka, Maria; Małecka-Wojciesko, Ewa; Radwan, Piotr; Reguła, Jarosław; Zagórowicz, Edyta; Banasiewicz, Tomasz; et al. (Gastroenterology Review/Przegląd Gastroenterologiczny, 2023)
This paper is an update of the diagnostic and therapeutic recommendations of the National Consultant for Gastroenterology and the Polish Society of Gastroenterology from 2013. It contains 49 recommendations for the diagnosis and treatment, both pharmacological and surgical, of ulcerative colitis in adults. The guidelines were developed by a group of experts appointed by the Polish Society of Gastroenterology and the National Consultant in the field of Gastroenterology. The methodology related to the GRADE methodology was used to assess the quality of available evidence and the strength of therapeutic recommendations. The degree of expert support for the proposed statements was assessed on a 6-point Likert scale. Voting results, together with comments, are included with each statement.